2017
DOI: 10.1002/jqs.2982
|View full text |Cite
|
Sign up to set email alerts
|

Flooding history of Lake Nakaumi, western Japan, inferred from sediment records spanning the past 700 years

Abstract: Management of flood risk can benefit from a knowledge‐based approach to flooding history. However, the data on such events are often insufficient for an objective evaluation of flooding characteristics such as their intensity. Therefore, we analyzed a 14C‐dated sediment core recovered from near the Iinashi River mouth in Lake Nakaumi, western Japan, and reconstructed flooding records over the past 700 years from rock magnetism, grain‐size distribution and sediment geochemistry. The sediment core contained thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…MS values can reflect relative changes in authigenic and terrestrial components, and increased erosion effects can lead to higher MS values (Dasilva et al, 2009; Støren et al, 2010). C/N ratios in lake sediments can be applied to identify organic matter sources, and higher C/N ratios suggest increased contributions from terrestrial sources (Ota et al, 2017; Pompeani et al, 2020). Here, we suggest that the proportion of coarse particles increased, which represented an increase in runoff and rainfall in the watershed and higher lake water levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS values can reflect relative changes in authigenic and terrestrial components, and increased erosion effects can lead to higher MS values (Dasilva et al, 2009; Støren et al, 2010). C/N ratios in lake sediments can be applied to identify organic matter sources, and higher C/N ratios suggest increased contributions from terrestrial sources (Ota et al, 2017; Pompeani et al, 2020). Here, we suggest that the proportion of coarse particles increased, which represented an increase in runoff and rainfall in the watershed and higher lake water levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lake sediments preserve continuous, integrated and high‐resolution records of past environmental changes in the catchment, which can be regarded as a reliable indicator of palaeoenvironmental change in the catchment (Chiverrell et al, 2019; Enzel et al, 1999; Lehnherr et al, 2018; O'Reilly et al, 2003). Studies have shown that changes in sedimentary particle size spectra, geochemistry and magnetic characteristics can provide evidence of past floods and environmental changes (Albrecher et al, 2019; Arnaud et al, 2016; Chen et al, 2017; Enzel et al, 1999; Ota et al, 2017; Støren et al, 2010). For example, Zhao et al (2015) used high‐resolution pollen and grain‐size records from Balikun Lake to reconstruct the history of water level fluctuations and climate change during MIS2 in the eastern region of the Tianshan Mountains, Central Asia.…”
Section: Introductionmentioning
confidence: 99%
“…The sand fraction (> 63 µm) is also found in modern river sediments although the percentage is typically low. A single extreme rain event under an arid climate could lead to an abrupt sand fraction increase (Ding et al, 2005;Liu et al, 2016;Ota et al, 2017;Zhou et al, 2018). Therefore, the sand fraction is mainly transported by winds and any peak or abnormal increase of the coarse grain size (especially the sand fraction) is likely related to flood events.…”
Section: Patterns and Interpretation Of The Proxiesmentioning
confidence: 99%
“…Therefore, the combined results obtained from the Pearson's Correlation Coefficient and the Principal Component Analysis indicate the association of major and trace elements with detrital materials rather than biogenic components. Harnois 1988) have been widely used to infer intensity of weathering (e.g., Ota et al 2017;Anaya-Gregorio et al 2018;Raza and Mondal 2018;Tawfik et al 2018;Hossain et al 2018;Kettanah et al 2020). However, a few authors (Cullers 2000;Buggle et al 2011;Garzanti et al 2015) documented that sediments are affected by various factors like sorting, recycling, and having significant proportions of carbonate or phosphate minerals.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%